Anomalous Switching of the Bi-Stable Percept of a Necker Cube: A Preliminary Study - Bierman, Dick (Journal of Scientific Exploration, 2011)
Psychophysiological research has shown anomalous correlations between unconscious states reflected by physiological fluctuations and random future conditions. Where the future conditions concerned emotional and neutral events, this anomalous effect has been called presentiment. In the present research, the domain of interest regarding apparent retrocausal effects is further extended to the visual experience of a so-called “transparent” Necker cube. When a picture of this cube is presented to subjects, their experience switches spontaneously between two viewpoints. In one perspective the cube is experienced as observed from “above,” in the other it is experienced as observed from “below.” We measured switching times from “the above” to “the below” experience. Once the subject had indicated by pressing a button that this shift had taken place, the picture of the transparent cube changed into an opaque presentation of one of the two possible viewpoints. The choice of which perspective was presented, “from above” or “from below”, was random. When the opaque view was “from above” this corresponded to the view for which the duration was measured (congruent), the opaque view “from below” was the incongruent condition. Arguing that in the incongruent condition the opaque view would “retrocausally” interfere with the “top view” for which the duration was measured, we predicted that in that condition the duration would be shorter. The switching-time effects found in the pilot and two confirmatory studies were in the same predicted direction. The pooled results showed a mean difference in switching time of 126 msec. These results seem to fit into a growing database of anomalous correlations between conscious and unconscious behavior and random future conditions. It extends the domain of these anomalous correlations to other non-emotional events. Alternative possibilities, such as procedural errors, are discussed. Keywords: time symmetry—retroactive interference—anomaly—retroactive priming—Necker cube